THE IMPLEMENTATION OF THE RURAL POLICY ABOUT SEA CONSERVATION (CASE STUDY IN MERPAS VILLAGE, KAUR REGENCY, BENGKULU) - Muhamad Arby Hariawan (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2025)
This paper comprehends implementation of the rural sea protection regulation in Merpas Village. As a village in Kaur Regency, Bengkulu Province, conserving the sea is a mandatory action due to massive needs from the public for marine-related resources. Research is designed as qualitative descriptive. Then, required data was obtained by several techniques namely: field trips, doing observation, in-depth interviews, studying literature, and making focus group discussion with Merpas Village’s stakeholders. Moreover, the theory of policy implementation gap was considered as the grand theory for this research. Results of study reveal that formulation of the rural regulation about sea has not regulated about the violation which is still done by communities outside Merpas. Then, for the operationalization process, villagers have followed the rural regulation such as never using trawl, compressor, and other forbidden activities for fishing. Also, the temporary closing area for fishing has been implemented by villagers of Merpas. However, fishermen from other locations are still seen using those techniques in Merpas. In the last point, the collaboration process has been done optimally for the internal stakeholders. The village has responsibility to maintain relationships with external stakeholders due to the fact that they could synergize in protecting sea-related territory of Merpas Village. From the study, the researcher suggests several points: making mutual understanding with the nearby village to respect the regulation, doing law enforcement to people who violate the rule, and improving external stakeholders.